Pemberdayaan Pendidikan Ekonomi Kreatif Melalui Pelatihan Pembuatan Tipung Untuk Masyarakat Desa Tunggularum - Zahwan Z, Muhammad Nazhri; Risabella, Cindy Angelina; Wardani, Kuntum Putri; Lutfitasari, Ika Madya; Aeni, Okti Aulia Hikmatul; Prabaswara, Murfid Zuhdi; Fadly, Muhamad Mufid; Syahda, Tsaqif Ikhsanaqi; Aqilla, Naufal Daffa; Alhafizh, Muhammad Dio; Humaini, Arif (Universitas Muhammadiyah Yogyakarta, 2025)
The main issue faced in Tunggularum Village is the dependence of snake fruit farmers on the supply of baskets from outside the village, despite the abundant availability of bamboo as raw material. This program is designed to provide training to the PKK (Empowering Family Welfare) women to enable them to produce baskets independently, reduce expenses during the harvest season, and open up business opportunities based on local resources. The community service program in Tunggularum Village aims to enhance the economic independence of the community through training in the production of bamboo-based baskets or snake fruit containers. The method used in this program is a participatory approach, which includes three main stages: socialization through meetings with the PKK women and RT (neighborhood association) savings groups, hands-on training with guidance from instructors and students, and evaluation of the training outcomes. The results of this program show a significant improvement in skills, where participants' success in making baskets increased from 30% in the initial stage to 85% in the final stage. This program successfully encouraged the community to become more independent in meeting their own basket needs and opened up business opportunities based on bamboo crafts in Tunggularum Village